2018
DOI: 10.1111/cfs.12446
|View full text |Cite
|
Sign up to set email alerts
|

Factors that determine decision making in child protection investigations: A review of the literature

Abstract: The aim of the study was to conduct a systematic review of the literature on factors that determine decision making in child protection investigations. More specifically, to investigate the existing research on the 4 factors that are considered fundamental for child protection decision making: case characteristics, caseworker characteristics, organizational characteristics, and external factors. The results indicated that child welfare decisions to investigate a case and/or to implement services are influenced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 34 publications
0
21
0
4
Order By: Relevance
“…The choice of interventions in child removal decisions can vary from one CPS investigator to the next (Bhatti‐Sinclair & Sutcliffe, 2018; Hughes & Chau, 2013), with some investigators more likely to gravitate to child removal (Doyle, 2007). There are a few predictors of the decision‐making of workers to investigate or remove children, including: case factors (child race/ethnicity, gender, age, and socio‐economic status) but not the child's point of view; parental substance abuse; CPS organizational factors; and investigator characteristics – experience, stress level and personality (Lauritzen et al, 2018).…”
Section: Ipv Victims Barriers Of Virtual Court and The Concept Of Dis...mentioning
confidence: 99%
“…The choice of interventions in child removal decisions can vary from one CPS investigator to the next (Bhatti‐Sinclair & Sutcliffe, 2018; Hughes & Chau, 2013), with some investigators more likely to gravitate to child removal (Doyle, 2007). There are a few predictors of the decision‐making of workers to investigate or remove children, including: case factors (child race/ethnicity, gender, age, and socio‐economic status) but not the child's point of view; parental substance abuse; CPS organizational factors; and investigator characteristics – experience, stress level and personality (Lauritzen et al, 2018).…”
Section: Ipv Victims Barriers Of Virtual Court and The Concept Of Dis...mentioning
confidence: 99%
“…This indicates a potential vector for bias as these predictors are singly scored by caseworkers and are influenced by caseworkers' own impression of the family. As illustrated by prior studies, a caseworker's opinion of risk may account for most of the variance in whether children are removed from their homes, even when it comes to quantitative tools [14,25,31]. For example, a caseworker who is struggling to engage with a family may feel that the caretakers are not taking appropriate steps to protect their child by accepting the worker's assistance, or that the caretakers do not have the skills or disposition required to nurture their child due to their rejection of interventions.…”
Section: Discrepancies Between Narrative Coding and Warm Risk Factors...mentioning
confidence: 99%
“…However, worker bias may be embedded in algorithms themselves, offering a veneer of standardization that disguises the degree to which algorithmic risk scores still represent potentially faulty risk assessment. In some cases, a worker's opinion of risk may account for most of the variance in whether children are removed from their homes, even when it comes to quantitative tools [14,25]. For a variety of systemic reasons, child-welfare caseworkers nationally have an average of less than two-years of work experience in their positions [12].…”
Section: Introductionmentioning
confidence: 99%
“…This latter review identified only three studies, all of which were poor quality, and highlighted a general lack of robust research to inform screening practices. Another systematic review by Lauritzen, Vis, and Fossum (2018) summarized the factors associated with multiple CPS decisions (i.e., decisions to investigate, dismiss, substantiate, and refer families for services) from studies published since 2005 that employed a broad array of methodologies. Over the past 35 years, several studies have been undertaken to build knowledge to inform technical approaches to decision‐making at the point of CPS intake.…”
Section: Conceptual Framework For Child Welfare Decision‐makingmentioning
confidence: 99%